Perawatan Payudara pada Ibu Nifas dengan Kejadian Bendungan ASI (STIKES dan AKZI Karya Husada Kediri, 2023)
The puerperium begins 2 hours after the birth of the placenta until 6 weeks. Problems that often arise during the puerperium, especially in terms of breastfeeding, are breast milk engorgement. One of the efforts to facilitate the release of breast milk and prevent the occurrence of breast milk engorgement by doing breast care. The purpose of this study was to analyze the effect of breast care on the incidence of breast milk engorgement in postpartum women at PMB Indah Maharani Singosari Malang. Quantitative research design with Quasy Experiment research method with pretest posttest control group design. The sampling technique used was purposive sampling. The research sample was 10 respondents in the treatment group and 5 respondents in the control group. The instruments used were SOP for breast care and Six Point breast Engorgement Scale (SPES) observation sheet. Data were analyzed using univariate analysis and multivariate analysis. The results of the pretest study with all respondents (100%) experiencing breast milk dams. Posttest results 10 treatment groups (100%) did not experience breast milk engorgement, 4 control groups experienced breast milk engorgement (90%), 1 control group did not experience breast milk engorgement (10%). The results of the analysis using the Mann Whitney test showed a ρ value of 0.004 <0.05. The conclusion is that there is a significant difference between the groups before and after the breast care intervention/treatment. Based on the results of this study, postpartum women can increase their knowledge about breast care during the postpartum period and breastfeeding to prevent of breast milk engorgement.